1 Albert G. Hodges, A Digest of the Statute Laws of Kentucky 788 (1834) - (:unkn) unknown (My University, 1834)
That whosoever shall hereafter use any fire-hunting or the killing of any deer by such means on any patented land, every person present at such fire hunting shall forfeit and pay twenty shillings for every such offense; and if any Indian be found fire-hunting as aforesaid, it shall and may be lawful for the owner of such land, or his or her overseer, to take away the gun of such Indian, and the same to keep to his own use.
Keywords: HUNTING REGULATION